The Role of Karimun Regional Government Pr in Establishing Partners with Mass Media - Haryati; Said Nuwrun T; Kasirul Fadhli; Mitra Yati; Suci Ayu Reza (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze how the role of public relations in the Regional Government of Karimun Regency in establishing partners with the mass media. The researcher used the role of public relations theory approach proposed by Cutlip et al. Methods of data analysis in this study using the Miles and Huberman methods, namely data reduction, data presentation and drawing conclusions. From the analysis that has been carried out, the results of this research are that Public Relations of the Regional Government of Karimun Regency in cooperating with local mass media has formal and informal forms of cooperation, but only media that has been verified through the press council can collaborate.